Treaty implementation in Caribbean law and practice - Anderson, Winston (1998)
Examines some of the effects that the transformation rule has produced in Caribbean law. Evaluates the extent to which recent developments, assimilate or approximate the monist doctrine, which is enjoying a resurgence in European law.